PENGGUNAAN MULTIMEDIA PEMBELAJARAN INTERAKTIF UNTUK MENINGKATKAN KETERAMPILAN MENULIS ENGLISHSIMPLE SENTENCESPADA MATA KULIAH BASIC WRITING DI STKIP GARUT - Darmawan, Deni; Setiawati, Pipih; Supriadie, Didi; Alinawati, Muthia (PEDAGOGIA, 2017)
Basic Writing is the first basic writing course for students in English Education Program of STKIP Garut, which is aimed to develop students' writing English skill. The efforts have been developed to improve the learning on Basic writing course and one of them is the use of multimedia. The research questions of this research were: 1). does the use of Computer-Assisted Instruction can improve the students' writing skill?, 2). does the conventional media also improve the students' writing skill?, 3). Is there any significant of improvement between the use of Computer-Assisted Instruction and conventional media?. The research used the quantitative approach and was conducted through the Quasi-Experimental Design. The research conducted between two classes, the experiment and control class, by using 50 students as samples in English Education Program of STKIP Garut. The research findings showed the primary points that the use of Computer-Assisted Instruction improved the students’ writing English simple sentence skill due to the gain value with the medium category on Basic writing course in STKIP Garut; The students’ writing English simple sentence skill of control class, which the students did not use the interactive instructional multimedia, improved considering the gain value with the low category; and There was the significance level of difference that the students who used the Computer-Assisted Instruction were better than the students who did not use the Computer-Assisted Instruction or on the other hand used the conventional media.